Criminology - Lamarca Pérez, Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Criminology is a science that making use of empirical methods studies criminal behavior and the ways in which society reacts. Based on the premise that crime constitutes a social problem, criminology analyzes the factors that may affect and lead to crime, giving special attention to victimology studies and types of social control established to prevent and treat crime.